Development of Control Board of Microcontroller Based Automatic Cow Scratching Machine - Murat Koklu; Kadir Sabanci; Cevat Aydin (International Journal of Applied Methods in Electronics and Computers, 2015)
The use of cow scratching machines in dairy cow farms is increasing. By using automatic scratching machines, animal are cleaned, the pores in the skin are opened and stimulating blood circulation is accelerated so that animals relieve. In addition; the performance of the herd arises due to the increasing yield of milk. The costs of the cow decrease accidents are prevented because they no longer rub up against something to scratch themselves. In recent years, developments in microcontroller and sensor technology have cheapened the prices of microcontroller and sensor. Microcontrollers and sensors began to be widely used in agricultural fields as in a lot of industrial areas because of technological advances and being cheap economically. In the study a control board is designed to automate the animals scratching machine. In the control circuit of automatic cow scratching machines, motion sensor detecting that the animals lean against the brush and PIC 12F675 microcontroller that activate brush motor according to the information of sensors are used.